Association of Serum Vitamin C With NAFLD and MAFLD Among Adults in the United States - Xie, Zhi-Qin; Li, Hong-Xia; Tan, Wen-Liang; Yang, Lei; Ma, Xiao-Wu; Li, Wen-Xin; Wang, Qing-Bin; Shang, Chang-Zhen; Chen, Ya-Jin (Frontiers in Nutrition, 2022)
Background and Aims: Despite remarkable progress of metabolic dysfunction-associated fatty liver disease (MAFLD), formerly named nonalcoholic fatty liver disease (NAFLD), the disease remains poorly improved. Since increased oxidative stress and inflammation contribute to the initiation and progression of fatty liver disorders, vitamin C (VC), an antioxidant agent, might be a suitable treatment option for MAFLD. However, the lack of clinically confirmed benefits makes clinicians challenging to recommend antioxidant supplements for MAFLD individuals. Methods: Herein, the nationally representative National Health and Nutrition Examination Survey (NHANES2017-2018) data were collected to evaluate the potential association between the serum VC levels with the risk of different categories of NALFD and the newly proposed MAFLD terminology. Hepatic steatosis was defined as controlled attenuated parameter scores≥263dB/m, whereas liver fibrosis status was defined as F0-F4, with the cutoff values of median liver stiffness being 6.3, 8.3, 10.5 and 12.5 (KPa), respectively. A cross-sectional analysis was performed to calculate the odds rate and determine the potential beneficial effects from VC. Results: A total of 4494 participants aged older than 18 years and conducted transient elastography examination were included. Our findings demonstrated that participants with increased serum VC status were more likely to be female predominant, more educated, and moderate-drinkers. Interestingly, female participants tended to have a lower prevalence of NAFLD, MAFLD, liver fibrosis, and cirrhosis after stratification by gender. Moreover, our results revealed that participants from quartile 3 group (50.5-67.0 µmol/L) experienced a slightly lower risk of MAFLD than the risk of NAFLD. Of note, the serum concentration of VC (quartile 2: 30.9-50.5 µmol/L) inversely associated with liver fibrosis and cirrhosis was lower than the serum VC level (quartile 3) associated with NAFLD and MAFLD. Notably，individuals from quartile 3 group experienced a statistically significant 32.5%, 42.0%, 45.7%, and 71% decrease in risk of NAFLD, MAFLD, liver fibrosis, and cirrhosis, respectively. Conclusions: In summary, our findings suggested an inverse association between serum VC levels and NAFLD, MAFLD, liver fibrosis, or cirrhosis. Additionally, adjustment of VC supplementation according to age, gender, and ethnicity may be a promising candidate for these diseases.